2014
DOI: 10.1016/j.ijrobp.2014.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of 18FDG-PET With CT Coregistration for Radiation Treatment Planning of Lymphomas and Other Hematologic Malignancies

Abstract: Purpose This prospective single-institution study examines the impact of positron emission-tomography (PET) using 2-[18F] fluoro-2-deoxyglucose and CT scan radiation treatment planning (TP) on target volume definition in lymphoma. Methods and Materials 118 patients underwent PET/CT TP during 6/2007-5/2009. Gross tumor volume (GTV) was contoured on CT-only and PET/CT studies by radiation oncology (RO) and nuclear medicine (NM) for 95 patients with positive PET scans. Treatment plans and dose-volume histograms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…From a clinical toxicity standpoint, reporting of differences in PTV instead of GTV is a more clinically meaningful interpretation of observed differences. This was consistent with prior reports of similar studies utilizing 18 F-Fluoro-ethyl-tyrosine (FET) based RT contouring [13] , [14] , [15] .…”
Section: Discussionsupporting
confidence: 92%
“…From a clinical toxicity standpoint, reporting of differences in PTV instead of GTV is a more clinically meaningful interpretation of observed differences. This was consistent with prior reports of similar studies utilizing 18 F-Fluoro-ethyl-tyrosine (FET) based RT contouring [13] , [14] , [15] .…”
Section: Discussionsupporting
confidence: 92%
“…5,16 18-Fluorodeoxyglucose (FDG) positron emission tomography (PET) is critical for accurate staging and may modify RT volumes. [17][18][19][20][21][22][23][24][25] PET does not obviate the need for contrast CT to delineate (for example) mediastinal lymphadenopathy, or magnetic resonance imaging (MRI) to define head and neck involvement. Smallvolume disease not evident on PET may be visible on CT or MRI.…”
Section: Imaging Considerationsmentioning
confidence: 99%
“…47 Another study evaluated 95 treatment sites in both HL and non-Hodgkin lymphoma and found similar results. 40 In summary, these studies concluded that the incorporation of FDG-PET has a significant impact on target definition in ISRT and INRT volumes for both HL and non-HL.…”
Section: Impact Of Pet/ct On Target Volume Definitionmentioning
confidence: 85%
“…As discussed earlier, extranodal marginal zone lymphomas, small lymphocytic lymphoma, and cutaneous T cell lymphomas have variable FDG uptakes, 3 and FDG-PET/CT might underestimate the extent of disease or miss it altogether. [40][41][42][43][44] Some anatomic sites have high level of physiologic FDG uptake, making visualization of lymphoma more difficult, such as primary central nervous system lymphoma (FDG uptake in normal brain tissue) and bowel lymphoma 45 (FDG uptake in normal bowel). Alternative imaging modalities are discussed later.…”
Section: Impact Of Pet/ct On Target Volume Definitionmentioning
confidence: 99%